Zero to 1, 600 m/s in 40 microns: Sensitive pulse shaping for materials characterization on Z. (2017) - Porwitzky, Andrew J.; Seagle, Christopher T.; Jensen, Brian J.
Abstract: Dynamic materials properties experiments on Sandia National Laboratories Z Machine require increasingly precise electrical current pulse shaping. In the experiment described here, a copper flyer plate is accelerated from rest to 1, 600 m/s over a 40 micron flight gap in 50 ns. This flyer then impacts a cerium sample, shock melting the cerium, before subsequent quasi-isentropic ramping to mega-bar pressures. Through predictive simulations, postdicted analysis, and a new computational tool for characterizing inherent Z Machine timing accuracy, qualitative estimates of pulse controllability and experimental design robustness are arrived upon.